Understanding the Integrated Pathways and Mechanisms of Transporters, Protein Kinases, and Transcription Factors in Plants under Salt Stress. (13th April 2021) - Shah, Wasifa Hafiz; Rasool, Aadil; Saleem, Seerat; Mushtaq, Naveed Ul; Tahir, Inayatullah; Hakeem, Khalid Rehman; Rehman, Reiaz Ul
Abstract : Abiotic stress is the major threat confronted by modern-day agriculture. Salinity is one of the major abiotic stresses that influence geographical distribution, survival, and productivity of various crops across the globe. Plants perceive salt stress cues and communicate specific signals, which lead to the initiation of defence response against it. Stress signalling involves the transporters, which are critical for water transport and ion homeostasis. Various cytoplasmic components like calcium and kinases are critical for any type of signalling within the cell which elicits molecular responses. Stress signalling instils regulatory proteins and transcription factors (TFs), which induce stress-responsive genes. In this review, we discuss the role of ion transporters, protein kinases, and TFs in plants to overcome the salt stress. Understanding stress responses by components collectively will enhance our ability in understanding the underlying mechanism, which could be utilized for crop improvement strategies for achieving food security.